Life Cycle Cost Gedung Masjid Sahid Universitas Veteran Bangun Nusantara - Fa-izah, Aprilina Nur; Firdausi, Annisa Azhar; Safarizki, Hendramawat Aski (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
One of the Bantara University facilities is Sahid Mosque. This mosque was built as a result of a design competition in 2020. The building area is 682 m2. Construction was carried out for 1 year with a total budget is Rp. 3,989,519,570.00. the building was operated in 2022. Many building components are imported from abroad. However, in this building the Life Cycle cost (LCC) calculation has never been done. Operation and maintenance need to be taken into account in every building construction. Building maintenance is a very important activity in maintaining the condition and value of property. This activity involves a series of actions to change, update and repair building components so that they continue to function properly according to established standards. The aim of this research is to identify the LCC of mosque buildings over their 25 years services life. The calculation is carried out by describing the LCC components, namely initial costs, operational costs, maintenance, replacement, and demolition. Initial costs are obtained from design and preparation costs. Operational costs are obtained from interviews with the parties concerned. Maintenance is obtained from looking at the age of the component lines and is calculated based on the Sukoharho Regency AHSP. The results of the LCC calculation 25 years in 2022 for the Sahid Univet Mosque showed a total cost of Rp. 8.786.694.099 that: initial cost worth Rp. 5.285.031.300 (60.15%); operational costs worth Rp.1.439.754.354 (16.39%); maintenance costs worth Rp. 1.523.813.081 (17.34%); and replacement costs amounting to Rp. 538.095.364 (6.12%).